In Memoriam Martine Broda - Veyrat, Miguel (Anales de Filología Francesa, 2009)
The author introduces the French poet and essayist Martine Broda. After recalling some concepts from “L’amour du Nom”, an essay on love lyricism and poetry, the author presents “Deslumbramientos” -his own translation of «Éblouissements» –as well as some concepts of the Brodian poetics: the link between poetry and language, the role of the horror and the unnameable, the ethical dimension of poetry, the illumination of the other... This article ends with 7 poems by Broda and their translation into Spanish by Veyrat.